The Relationship Between Antihypertensives Use And Uncontrolled Blood Pressure In Chronic Kidney Disease With Routine Hemodialysis - Pulungan, Yulianasari; Endro Nugroho, Agung; Pramantara, I Dewa Putu (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2025)
Hypertension in end-stage chronic kidney disease (CKD) patients undergoing HD is difficult to control. The aim of the study was to determine the relationship between the number of antihypertensive medications taken and the use of dialyzed antihypertensive medications on uncontrolled blood pressure in CKD patients on hemodialysis. Consecutive sampling was employed in a retrospective cohort study. Data collection for the study took place in July 2023 at Temanggung Regional Hospital. The inclusion criteria in this study were CKD patients who undergoing routine hemodialysis twice a week, aged ≥ 18 years, and without or with comorbidities. Medical records and interviews with research participants were used to gather data. Forty-eight patients with clinical outcomes of uncontrolled predialysis blood pressure and four patients with regulated predialysis blood pressure made up the 52 research subjects. The number of antihypertensive drugs used is significantly associated with uncontrolled predialysis blood pressure in CKD patients with hemodialysis using antihypertensives (p-value 0,033). The use of dialyzed antihypertensive drugs is not associated with uncontrolled predialysis blood pressure in CKD patients on hemodialysis using antihypertensives (p-value 0,115).